Analisis Kepemilikan Institusional Tinggi Dan Rendah Terhadap Kinerja Perusahaan Di Indonesia - Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
This study examined based on data of companies in Indonesia about the relationship between institutional ownership and corporate performance. In particular, institutional ownership will be distinguished by a high institutional ownership and low institutional ownership in order to determine the specific impact of institutional ownership on the performance of companies in Indonesia. Data were analyzed using different test mean with a sample of 136 companies. This study shows that a high institutional ownership gives a higher impact on the performance of the company compared with a low institutional ownership. Therefore, it reinforces the finding that high institutional ownership impacts in its monitoring compared to low ownership and corporate performance.